Analysis of Sport Tourism Potential, Occupational Safety and Health in Tandem Paragliding - Supriyono, Supriyono; Setyawati, Heny; Kusuma, Donny Wira Yudha; Appukutty, Mahenderan; S, Adi (Jurnal Kesehatan Masyarakat, 2024)
This research aims to analyze the level of tourism security and safety in the tandem paragliding aspect in the Kemuning village area. The problem that arose was that there was a tandem paragliding accident, namely a tourist fell on Kemuning Hill, in this accident there was no insurance for tourist accidents. The research uses a mixed method model by taking into account the Kemuning paragliding tourism environment. Analysis of tandem paragliding tourism potential using SKKNI no. 157 of 2019 for tandem paragliding aerospace scouting. Data management uses SPSS 23, and the respondents studied are Kemuning paragliding tandem managers, paragliding tandem pilots, tourists, and parties concerned with the Kemuning tourism tandem. Located in Segoro Mountain, Kemuning Village, Ngargoyoso District, Karanganyar Regency. The research results show that tourism safety data for tandem paragliding in Kemuning village is in the Very Suitable category. There needs to be a new sports tourism sector that supports the main tourism so that it can increase community income and increase the health of tourism visitors.